Development of A Knowledge•Based Compliance Auditing System for Environmental Impact Assessment (EIA) Projects in Malaysia - Rahman, Md. Mizanur (2001)
Environmental Management Program (EMP) constitute an important component of the Environmental Impact Assessment (EIA) report of the development projects where the environmental monitoring programs and the environmental compliance auditing (ECA) aspects should be described in detail. ECA requires systematic selection of monitoring variables and analysis of the monitoring database and also requires that a uniform quality standard in auditing be maintained for different types of development projects and different stages of their development. ECA should produce an audit report that is easy to understand and could be used under taking mitigation measures. Presently, in Malaysia, for the EIA projects, there is neither any specific guideline for conducting compliance auditing nor any systematic management of the data generated through monitoring of the projects. The main objective of this study is to develop a knowledge-based environmental compliance auditing system (called ECA-KB) that uses expert's knowledge from different environmental fields and a quantitative technique of evaluating the environmental compliance level of a particular project. ECA-KB comprises of three components namely monitoring database system, compliance auditing model, and knowledge base system. These three component systems have been integrated together to produce concise and comprehensive environmental compliance audit report for the EIA projects. The study provides a tool for the decision-makers and the stakeholders namely the project proponents, environmental consultants, and Department of Environment (DOE) to monitor, evaluate environmental compliance level of the projects, generate compliance audit report, and to keep track on the compliance trend. The great potentiality of the developed ECA-KB is that it is produced in easy interactive and simplified manner that can be run as desktop applications by both the experts and the non-expert users. The system is available in install able CD's and can be reached to the potential users by several ways including distribution of CD's through market channel, demonstration in the seminars, and symposium.